Uso da realidade aumentada no ensino da geometria espacial - Dantas, Elania Hortins (2018)
This work presents a study about the use of new technologies in the teaching of Mathe- matics, more speciﬁcally, the use of Augmented Reality as a tool to assist in the teaching of Spatial Geometry. From the observation of the diﬃculties faced by students in the understanding and interpretation of mathematics, from the view that most of them have that mathematics is a diﬃcult discipline, as well as the fact that we are dealing with a generation totally focused on the technologies, the production of this work is necessary. We present the basic theory at geometric solids, a step-by-step tutorial necessary for the production and application of an RA project, a methodological proposal on how to use RA for better visualization and, consequently, a better understanding of the geometries solids through suggested activities. The application of this work was consolidated with high school students of a public school - IFRN campus Caic´o. The practice for analysis and conclusions was made through an application of the Spatial Geometry content using an Augmented Reality project, making this technological tool an attractive pedagogical resource capable of bringing the attention and curiosity of the student, thus promoting their autonomy learning.